PENGARUH DANA ZAKAT MAL DAN SSEDEKAH UNTUK KINERJA UMKM DI DUSUN PLUMPUNGREJO DESA KARANGTENGAH KECAMATAN KANDANGAN KABUPATEN KEDIRI - M. Afani Almaarif; Dwiyani Sudaryanti; Hariri Hariri (Universitas Islam Malang, 2022)
This study aims to determine the effect of zakat mal and sodaqoh on the performance of micro, small and medium enterprises in Plumpungrejo hamlet, Karangtengah village, Kandangan sub-district, Kediri district. The type of research used is research with a quantitative approach. Based on the results of research conducted by researchers by distributing questionnaires to owners of micro, small and medium enterprises in Plumpungrejo hamlet, researchers obtained 62 respondents based on owners of micro, small and medium enterprises who received zakat mal and shodaqoh funds. Sampling of this study used the census sampling technique. The analytical tool used is using SPS. The results of the study prove that the zakat mal variable (X1) does not have a positive and partially significant effect on the performance of micro, small and medium enterprises (Y) and the shodaqoh variable (X2) does not have a positive and significant effect on the performance of micro, small and medium enterprises (Y).